Policy analysis in national security affairs new methods for a new era - Kugler, Richard L. (Washington, D.C National Defense University Press, 2006)
This book is intended to help fill a void in the literature while making a contribution to public awareness. Most books on national security affairs focus on substantive issues, such as nuclear proliferation, arguing in favor of one policy or another. This book addresses something more basic: how to conduct policy analysis in the field of national security, including foreign policy and defense strategy. It illuminates how key methods of analysis can be employed, by experts and nonexperts, to focus widely, address small details, or do both at the same time. To my knowledge, there is no other book quite like it.
Includes bibliographical references (p. 619-626) and index.
Keywords: National security--Methodology.